Bibliometrics Analysis on “Role of Library in Supporting Knowledge Management” Published During 1999-2020 - Tupan Tupan; Retno Asihanti Setiorini (Program Studi Ilmu Perpustakaan UIN Alauddin, 2020)
Libraries must play a role in knowledge management created by all academicians so that it can be used by anyone. This study analyzes publications about the role of libraries in supporting knowledge management. The data were obtained from the Scopus database. The retrieval technique is by entering the keywords